Peningkatan Kompetensi Aplikasi Komputer Akuntansi di Wilayah SMK Bregaslang sebagai Persiapan Uji Kompetensi Kejuruan - Dewi Kartika; Yeni Priatna Sari; Fitri Priatna Amaliyah; Arifia Priatna Yasmin; Siti Ma’rifatul Muawanah (Universitas Muhammadiyah Semarang, 2025)
The development of information technology is currently growing rapidly, causing users and developers of information technology to adapt quickly to keep up with these developments. The purpose of this community service is to provide knowledge and skills to accounting students about the use of accounting computer applications needed by companies. The stages of implementation of this activity include the preparation stage, the implementation stage, and the evaluation stage. The method of implementing this community service activity is the delivery of material followed by direct practice using accounting computer applications. The implementation method is divided into three stages: identifying problems, implementing activities, and evaluating results. In the first stage, the PKM team conducted surveys and interviews at several vocational schools in the Bergaslang area. The second stage, namely the implementation of activities, was carried out by giving lectures, tutorials, and discussions. The final stage, namely evaluation, was carried out by giving pretests and posttests to all PKM participants. Based on the results of the presentation of material delivered by the team of lecturers about improving the competence of accounting computer applications in the Bregaslang Vocational School area as preparation for the vocational competency test, the results were that all participants were able to follow the flow of the material guided by the team of lecturers and were able to carry out the practice of preparing financial reports using Accurate properly. The training conducted has shown an increase in students' skills in improving their computer accounting application competency in the Bregaslang Vocational High School area as preparation for the vocational competency test.